2015
DOI: 10.5688/ajpe79569
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Student Performance and Confidence with a Standardized Patient and Standardized Colleague Interprofessional Activity

Abstract: Objective. To assess the impact of a standardized patient and standardized colleague interprofessional activity on student performance and perceived confidence in communicating with patients and physicians. Methods. Students in the third professional year were presented with a practice and final activity including a standardized patient interaction, SOAP note preparation, and standardized colleague interaction. Student performance was measured by assessment rubrics on practice and final activities. Students' p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“…26 Standardized patient colleagues have been used to further IPE in pharmacy education in recent projects. 17,27,28 In each instance, the standardized colleagues portrayed different types of medical doctors with variation in level of training (from medical student to seasoned attending) and specialty. In our project, we did not collaborate with physicians or medical students, but instead included a broad range of the disciplines that would be found in a larger care team.…”
Section: Discussionmentioning
confidence: 99%
“…26 Standardized patient colleagues have been used to further IPE in pharmacy education in recent projects. 17,27,28 In each instance, the standardized colleagues portrayed different types of medical doctors with variation in level of training (from medical student to seasoned attending) and specialty. In our project, we did not collaborate with physicians or medical students, but instead included a broad range of the disciplines that would be found in a larger care team.…”
Section: Discussionmentioning
confidence: 99%
“…Siempre parte de los datos clínicos obtenidos del paciente, los cuales precisan una sistemática para su adquisición y registro que permita un adecuado intercambio de información entre profesionales 2 . Estos registros sistematizados, como el que se introduce en nuestro estudio, también se consideran muy útiles para la educación médica [14][15][16] , ya que permiten a los estudiantes y residentes formarse y entrenarse para afrontar el proceso asistencial, una situación siempre ligada a unos altos índices de variabilidad y, por tanto, de difícil transmisión docente 17 , con buenos resultados publicados en diversos estudios 3,18 . Asimismo, el uso integrado de estos conceptos en la HCE ha permitido mejorar la calidad asistencial y la eficiencia, e incluso se propone como mecanismo para reducir los errores médicos ligándolos a estrategias en relación con la seguridad del paciente 19 y el gasto sanitario.…”
Section: Criteriosunclassified
“…Using SPs in communication skills and counseling in pharmacy still seems to be a newborn. However, studies have shown that SP is used for training and assessment purposes in recent year,[ 16 17 ] but seldom used for evaluating the quality control of their performance as a valid assessment method.…”
Section: Introductionmentioning
confidence: 99%